The Structure and Purpose of Management in Ensuring Economic and Financial Stability - Akramova Aziza Abduvohidovna (Scientific Trends, 2023)
The article highlights the features that determine, influence, optimize the management structure and implement management goals in ensuring economic stability. A series of basic requirements for the management goal and innovative goals are also mentioned. A tree of goals is described with the need to regulate relationships in management goals.
Keywords: Management structure, management goals, innovative changes, management functions and tasks, management methods, specific tasks, business strategy, goal tree.